2022
DOI: 10.3389/fphar.2022.918771
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Growth Factor and Cytokine Pathways to Treat Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease of unknown origin that usually results in death from secondary respiratory failure within 2–5 years of diagnosis. Recent studies have identified key roles of cytokine and growth factor pathways in the pathogenesis of IPF. Although there have been numerous clinical trials of drugs investigating their efficacy in the treatment of IPF, only Pirfenidone and Nintedanib have been approved by the FDA. However, they have some major limitations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 222 publications
1
47
0
3
Order By: Relevance
“…Chemokines and interleukins are also involved in recruitment of pro-fibrotic cells and formation of profibrotic microenvironment, as we discussed in our previous paper (Ma et al, 2022). However, CCL2, a key chemokine for monocyte/macrophage migration and infiltration, failed to demonstrate clinical benefit in a phase II clinical trial (NCT00786201).…”
Section: Summary Of Emerging Therapeutic Targets For Ipf In Drug Disc...mentioning
confidence: 96%
See 1 more Smart Citation
“…Chemokines and interleukins are also involved in recruitment of pro-fibrotic cells and formation of profibrotic microenvironment, as we discussed in our previous paper (Ma et al, 2022). However, CCL2, a key chemokine for monocyte/macrophage migration and infiltration, failed to demonstrate clinical benefit in a phase II clinical trial (NCT00786201).…”
Section: Summary Of Emerging Therapeutic Targets For Ipf In Drug Disc...mentioning
confidence: 96%
“…JAK/STAT signaling ( Montero et al, 2021 ), receptor-type tyrosine kinase/non-receptor-type tyrosine kinase signaling (e.g., Src) ( Hu et al, 2014 ), PI3K/Akt/mTOR signaling ( Hennessy et al, 2005 ; Mercer et al, 2016 ; Lawrence and Nho, 2018 ), and Hedgehog signaling ( Effendi and Nagano, 2021 ) comprise complex fibrosis regulatory signaling pathway. In our previous reviews, we have discussed the aforementioned signaling pathways ( Ma et al, 2022 ).…”
Section: Recent Progress In Therapeutic Targets and New Drug Developm...mentioning
confidence: 99%
“…IPF has the characteristics of rapid progression, high fatality rate and poor prognosis, and the median survival after diagnosis in most patients is 2.5 to 3.5 years, with a five-year survival rate of only 20–40% ( 6 ). The pathogenesis of IPF has not yet been elucidated, and anti-inflammatory therapy is generally used clinically with glucocorticoids, immunosuppressants, cytotoxic agents or inhibitor (Pirfenidone and Nintedanib) ( 7 9 ). With the deepening of clinical research, researchers found that only 20% of IPF patients are sensitive to glucocorticoid therapy, and often transgender reactions(allergies: it is a type of immune reaction, a reaction that occurs after non-peptide drugs are combined with the body’s protein as a hapten to an antigen), there is no specific treatment plan for IPF in the clinic, coupled with the lack of specific clinical manifestations in the early stage of IPF, so the difficulty of diagnosis and treatment is high ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quimiocinas e interleucinas también están involucradas en el reclutamiento de células profibróticas y en la formación de un microambiente profibrótico, como discutimos en un artículo anterior [207]. Sin embargo, CCL2, una quimiocina clave para la migración e infiltración de monocitos/macrófagos, no mostró beneficio clínico en un ensayo de fase II (NCT00786201).…”
Section: Avances Recientes En Los Blancos Terapéuticos Y El Desarroll...unclassified
“…La señalización JAK/STAT [214], la señalización de tirosina quinasa de tipo receptor/no receptor (por ejemplo, Src) [215], la señalización PI3K/Akt/mTOR [216–218) y la señalización Hedgehog (Effendi y Nagano, 2021) constituyen una compleja vía de señalización reguladora de la fibrosis. En revisiones anteriores hemos discutido estas vías de señalización [207].…”
Section: Avances Recientes En Los Blancos Terapéuticos Y El Desarroll...unclassified